DAMPAK GAYA KEPEMIMPINAN TERHADAP PRODUKTIFITAS DAN KEPUASAN KERJA KARYAWAN PERUSAHAAN ASURANSI - Soeharsono Soeharsono (Universitas Islam Balitar, 2016)
This study reports the difference between products of two kinds of leadership style in an insurance company in terms of productivity measured using total closing and amount of bonus obtained by the company in a two-year operayion and work satisfaction factor. The study was conducted in an insurance company in Malang. Data on work satisfaction were collected using questionnaire and data were analyzed using t-test for independent sample. The study revealed that supporting leadership style is superior in terms of productivity. Attainment on total closing and bonus within two-year operation as well as work satisfaction was significantly superior. AIA is recommended to implement situational leadership style to increase productivity of agency and to find added value in terms of work satisfaction of the agencies.